Recovery from transportation by road of farmed European eel (Anguilla anguilla). (12th September 2013) - Boerrigter, Jeroen G J; Manuel, Remy; van den Bos, Ruud; Roques, Jonathan A C; Spanings, Tom; Flik, Gert; van de Vis, Hans W
Abstract The objective of this study was to assess the effects of transportation of marketable eel (0.15 kg) in the Netherlands with respect to welfare. Eels (Anguilla anguilla) were obtained from a commercial farm and acclimatized for 7 weeks at the laboratory. Fish were transported according to regular commercial procedures. The animals were placed in water‐filled transport tanks on the trailer. Fish density increased from 72 kg m−3 (husbandry) to 206 kg m−3 (fasting) and was further increased to 270–290 kg m−3 during transport. Fish transport lasted 3 h after which the eels were returned to laboratory recirculation systems to measure parameters indicative of stress load, i.e. mortality, plasma cortisol, lactate and non‐esterified fatty acids (NEFA) as well as gill morphology. Samples were taken at 0, 6, 24, 48 and 72 h after transport in transported fish and non‐transported counterparts (controls). Transportation affected water quality within known tolerable limits. No mortality during or after transport was observed. After 6 h, plasma cortisol levels had returned to baseline. However, energy metabolism had increased suggesting that transportation of eels resulted in an increased energy demand that lasted for at least 72 h in the fasted animals. Thus, it is conceivable that exposure to adverse conditions, prior to stunning/killing, in a slaughterhouse may result in allostatic overload in eel.